1999
DOI: 10.1111/j.1749-6632.1999.tb09498.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Regional Lung Ventilation by Functional Electrical Impedance Tomography during Assisted Ventilationa

Abstract: A new approach in discriminating the regional air volume changes in the lungs associated with either spontaneous or mechanical ventilation during assisted ventilation is presented. Impedance data are obtained by conventional electrical impedance tomography (EIT). The data are filtered in the range of either the spontaneous or the ventilator rate and processed by the functional EIT (f-EIT) evaluation technique, whereby the variation of the respective EIT data with time is determined and imaged. EIT measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 26 publications
1
37
0
7
Order By: Relevance
“…The applied respiratory settings used in our study caused an end-expiratory lung impedance change of up to 0.12, which is 12%. Although all these assumptions are in fact violated during EIT measurements it has repeatedly been shown that meaningful results can be obtained with this method [21,22,23,24,6,25,26]. End-expiratory lung impedance change reflects impedance variations in one cross-section of the thorax, while EELV is a global parameter of the whole lung.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…The applied respiratory settings used in our study caused an end-expiratory lung impedance change of up to 0.12, which is 12%. Although all these assumptions are in fact violated during EIT measurements it has repeatedly been shown that meaningful results can be obtained with this method [21,22,23,24,6,25,26]. End-expiratory lung impedance change reflects impedance variations in one cross-section of the thorax, while EELV is a global parameter of the whole lung.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…In this way, two EIT images of regional lung ventilation showing either its mechanical or spontaneous component were generated from each EIT measurement. This evaluation approach is described in detail in [12].…”
Section: Electrical Impedance Tomography (Eit)mentioning
confidence: 99%
“…EIT is a relatively novel technique, validated against computed tomography and inert gas wash-out methods, for describing regional lung volume in animals and adults [18][19][20][21]. It has been used to describe regional ventilation in small cohorts of spontaneously breathing [16,25] and ventilated infants [30][31][32]. We have shown that EIT is both feasible and practical for individual assessment of regional ventilation in ventilated extremely preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…The relative DZ VT within each of the 32 anterior-to-posterior (gravitydependent) chest slices was determined by summing all the pixel values within each slice [25,30]. To simplify interpretation, the area under the curve (AUC) for the slices occupying the anterior, middle and posterior thirds of the chest, and the geometric centre of ventilation within the chest, was calculated [15,25].…”
Section: Distribution Of Tidal Ventilationmentioning
confidence: 99%